(untitled) (Baltic Journal of Sport and Health Sciences, 2022)
Background: It has been observed that old mice have a better tolerance to glucose than young after an intraperitoneal injection of glucose. We hypothesized that an intraperitoneal injection of glucose overestimates glucose tolerance in old mice. Methods: We assessed differences in glucose tolerance outcomes in 2- (young, n=23) and 23- to 27-month-old (old, n=23) male C57BL/6J mice after an intraperitoneal (IP) or intravenous (IV) injection, or oral gavage (OG) of glucose. Results: The area under the curve (AUC) of the changes of blood glucose concentration over 2 hours after glucose administration was lower in old than young animals (p<0.001). The AUC was higher after IV than either IP or OG (p<0.001). However, normalized to peak glucose concentration, the time course was similar in young and old animals, and was – except for an earlier peak in IV than OG (p=0.013) – independent of route of administration. Conclusion: We suggest that 1) to determine glucose tolerance the time course of changes in glucose concentration rather than the AUC, which is significantly affected by excursion magnitude, is preferable; 2) glucose tolerance can be measured equally well with IP, IV and OG; 3) there is no significant age-related difference in glucose tolerance in mice. Keywords: glucose tolerance test, glucose uptake, aging, glucose intolerance, mice, diabetes.